"Armada Jaya XXX/11" naval exercise : Indonesia's naval strategy - Ristian Atriandi Supriyanto (2012)
Indonesia recently concluded a naval exercise close to disputed waters. This serves as a hint of Indonesia’s future naval contingency planning and broader military strategy.